New Zealand's Destination Image and the Chinese Outbound Market: A Comparative Study Between the Beijing (North) and Guangdong (South) Markets - Zhao, Chengcheng (Auckland University of Technology, 2006)
This thesis examines the similarities and differences between northern and southern Chinese markets (in this case, the Beijing and Guangdong markets) in relation to New Zealand's destination image, from both visitors' and tour guides' perspectives. Destination image issues focused on information source and cultural factors, as well as their interrelationships. The purpose of this research is to achieve a better understanding of the Chinese outbound market as well as the heterogeneous market characteristics in order to provide insight for the New Zealand tourism industry. This research involves both interviews with visitors and tour guides based on a grounded theory methodology. Analysis of the interviews was based on two research themes: factors influence New Zealand's destination image at different stages, as well as the Chinese regional market difference in relation to destination image. Interviews were also focused on two stages of destination image formation: pre-visit images and in-destination images. Difference between Beijing and Guangdong markets on the research themes during the different stages were explored and analyzed. Research findings showed that destination image is influenced by both the information source and the cultural factors for Chinese tourists. Moreover, regional difference existed in China in particular their perceptions about New Zealand, preferences and personal values. Most tourists consider pre-visit image is essential; however, New Zealand's image in China was not very impressive and effective. Before visitation, New Zealand's destination image is influenced heavily by information available in China. The way tourists search for information and the image they were attracted for coming to New Zealand between Beijing and Guangdong were different. During-visit impressions of New Zealand were considered by majority of the tourists to be better than their expectations. However, due to their different cultural backgrounds, Beijing and Guangdong tourists have different reactions to New Zealand's products, which can be reflected through different shopping behaviours, and different demands and satisfaction levels. Overall, segmenting the Chinese outbound market into regions is recommended for future marketing, in order to attract more visitors by providing more suitable products.
Keywords: Tourism - New Zealand; Tourism - China.; Tourism